2013
DOI: 10.1021/mp300543t
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Access of p53 to the Nucleus Regulates Its Proteasomal Degradation by MDM2

Abstract: The tumor suppressor p53 can be sent to the proteasome for degradation by placing its nucleo-cytoplasmic shuttling under ligand control. Endogenous p53 is ubiquitinated by MDM2 in the nucleus, and controlling the access of p53 to the nuclear compartment regulates its ubiquitination and proteasomal degradation. This was accomplished by the use of a “protein switch” that places nuclear translocation under the control of externally applied dexamethasone. Fluorescence microscopy revealed that sending protein switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The loss of MDM2 and p21 protein levels could be the result of changes in protein half-life on p53 activation as evidenced in published results where accelerated MDM2 autodegradation was reported during p53-mediated DNA damage response (17). However, p53 function and stability may also be tightly controlled by its subcellular localization (18,19). Therefore, it is possible that in a cell triggered into apoptosis, nuclear or mitochondrial localized p53 remains fairly stable following RG7388 washout, whereas MDM2 and p21 are accessible to be targeted by the cytoplasmic ubiquitin proteasome pathway.…”
Section: Discussionmentioning
confidence: 93%
“…The loss of MDM2 and p21 protein levels could be the result of changes in protein half-life on p53 activation as evidenced in published results where accelerated MDM2 autodegradation was reported during p53-mediated DNA damage response (17). However, p53 function and stability may also be tightly controlled by its subcellular localization (18,19). Therefore, it is possible that in a cell triggered into apoptosis, nuclear or mitochondrial localized p53 remains fairly stable following RG7388 washout, whereas MDM2 and p21 are accessible to be targeted by the cytoplasmic ubiquitin proteasome pathway.…”
Section: Discussionmentioning
confidence: 93%
“…For example, DNA damage induces the phosphorylation of p53 at Ser-15, Ser-20 and Ser-37, thereby weakening its binding to the oncogenic protein MDM2, which would otherwise promote the ubiquitination and proteasomal degradation of p53 [13]. Immunoprecipitation was performed to test whether PPM1F and p53 would form a complex after nicotine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The protein stability of p53 depends on the time required for its intracellular degradation. It has been reported that MDM2, an intracellular protein, binds to p53 [12] and exports it from the nucleus for ubiquitin-dependent proteolysis [13]. In response to DNA-damaging agents, posttranslational modifications such as the phosphorylation of Ser-15 [14, 15], Thr-18 [16], and Ser-20 [17] weaken the binding between p53 and MDM2.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, the E3 ligase murine double minute 2 (MDM2) binds to the MDM2 binding domain (MBD) of p53 prompting polyubiquitination of terminal lysines on the C-terminus of p53, which marks p53 for proteasomal degradation (2). Upon stress induction, such as DNA damage or ER stress, cytoplasmic p53 translocates either to the nucleus (3) or to the mitochondria (4).…”
Section: Introductionmentioning
confidence: 99%